308-nm Excimer Lamp vs. Combination of 308-nm Excimer Lamp and 10% Liquor Carbonis Detergens in Patients With Scalp Psoriasis: A Randomized, Single-Blinded, Controlled Trial - Rattanakaemakorn, Ploysyne; Triyangkulsri, Korn; Iamsumang, Wimolsiri; Suchonwanit, Poonkiat (Frontiers in Medicine, 2021)
Background: Scalp psoriasis is usually refractory to treatment. Excimer devices have been proved to be a promising therapeutic option in psoriasis. Greater efficacy of phototherapy can be achieved by concurrent use of coal tar derivatives. Objective: We aimed to compare efficacy and safety between 308‐nm excimer lamp monotherapy and a combination of 308‐nm excimer lamp and 10% liquor carbonis detergens in the treatment of scalp psoriasis. Methods: In this randomized, evaluator-blinded, prospective, comparative study, 30 patients with scalp psoriasis received either 308-nm excimer lamp monotherapy or a combination of 308-nm excimer lamp and 10% liquor carbonis detergens twice per week until complete remission of the scalp or for a total of 30 sessions. Efficacy was evaluated by the improvement of Psoriasis Scalp Severity Index (PSSI) score, itch score, and Scalpdex score. Results: Both treatments induced significant improvement in PSSI score with greater reduction observed in the combination group. At 30th visit, a 75% reduction in PSSI (PSSI75) was attained by 4 (28.6%) and 9 (69.2%) patients treated with monotherapy and combination therapy respectively (P < 0.05). Conclusions: Excimer lamp is well-tolerated in patients with scalp psoriasis and liquor carbonis detergens can be used as a combination therapy to improve the efficacy of excimer lamp.